Application of complex method of physical rehabilitation at a chronic obstructive bronchitis for men. - Bandurina E.V; Shpitalny E.N (Kharkov National Pedagogical University, 2012)
Directions of use of physical rehabilitation at a chronic obstructive bronchitis for men are considered. 20 patients, men in age 35 - 45 years, took part in research. Duration of course of rehabilitation made 20 days. A respiratory gymnastics is applied to on by the method of Strel'nikova, segmental massage, combination of phytotherapy and aromatherapy. Certain principles of the individual differentiated going near treatment of patients on the stationary and ambulatory stages of their rehabilitation. The stages of rehabilitation of patients are recommended. The improvement of indexes which characterize the drainage function of bronchial tubes and external breathing is marked. Positive influence of method is set on exchange processes and general firmness of organism. It is rotined that application of complex method of physical rehabilitation is reduced by duration of days of uncapacity, improves work to the cardio-respiratory systems, promotes adaptation and regenerative possibilities for patients.